Elevating the Community-Based Approach towards River Management: A Case Study of Squatter's Community in Inanam-Likas River Basin in Sabah, Malaysia - Dollah, Ramli; Jafar, Adi; Mohd Radzi, Marsitah; Sakke, Nordin; Mapa, Mohammad Tahir; Maraining, Amrullah (Indonesian Journal of Geography, 2023)
River pollution is one of the major threats to the environment worldwide, especially in developing countries such as Malaysia. Although numerous actions, policies and efforts to alleviate river pollution, the issue continues to hurt Malaysia’s environmental sustainability. Based on the case study of the Inanam-Likas river basin situated on the western coast of the state of Sabah, in East Malaysia, this paper proposes an integration of a more inclusive approach toward communities in river management. This paper suggests the inclusion approach in river management by squatter communities who are residents along the riverbanks as part of the stakeholders alongside governmental and non-governmental agencies. As such, this study introduces this approach as a community-based to the river management policy facilitated by the local authorities and other relevant agencies. Without community support, effective mitigation strategies and relevant policy toward river management, river pollution will continue to threaten environmental sustainability.